SEG Technical Program Expanded Abstracts 1999 1999
DOI: 10.1190/1.1821142
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal offset‐dependent attributes (AVO and FVO) applied to fracture detection

Abstract: Using the amplitude versus offset (AVO) and the frequency versus offset (FVO) information, the diagnostic ability of P-wave seismic data in fracture detection is investigated. The offset-dependent attributes (AVO and FVO) are estimated by using an eigenvector based estimation technique, the multiple signal classification frequency estimator. These attributes are applied to the determination of principal orientation of fractures in carbonate fractured reservoirs located in the Maporal field in the Barinas basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Classically, the spectral decomposition was useful in mapping thickness of conventional reservoirs. In reflection seismic exploration, although important work has been done in analyzing the change in spectra due to fractures (e.g., Sheni et al, 1999), relatively few studies have explored the relationship between spectral amplitude response to fracture intensity and scale (Gao, 2012), which can be instrumental in detecting fractures in unconventional reservoirs. Gao (2012) reported the implications of the Fresnel-zone texture for amplitude interpretation and suggested that Fresnelzone texture roughness and scale can cause selective frequency tuning that are in turn related to the fracture intensity and spacing (density) in unconventional fractured reservoirs.…”
Section: Fracture Detection In Central Appalachian Basinmentioning
confidence: 99%
“…Classically, the spectral decomposition was useful in mapping thickness of conventional reservoirs. In reflection seismic exploration, although important work has been done in analyzing the change in spectra due to fractures (e.g., Sheni et al, 1999), relatively few studies have explored the relationship between spectral amplitude response to fracture intensity and scale (Gao, 2012), which can be instrumental in detecting fractures in unconventional reservoirs. Gao (2012) reported the implications of the Fresnel-zone texture for amplitude interpretation and suggested that Fresnelzone texture roughness and scale can cause selective frequency tuning that are in turn related to the fracture intensity and spacing (density) in unconventional fractured reservoirs.…”
Section: Fracture Detection In Central Appalachian Basinmentioning
confidence: 99%
“…Since the early ideas proposed by Crampin 12 et al about the use of pre-stack seismic data to detect fractures, many teams [17][18][19][20][21][22][23][24] have exerted significant efforts to find practical ways to accomplish this. Unfortunately, this area turned out to be a very challenging scientific domain where the solutions seem to be very complex.…”
Section: Fracture Imaging Using Pre Stack Seismic Datamentioning
confidence: 99%
“…While coherence and amplitude gradients can often detect lineaments, reflector curvature is more directly linked to fracture distributions (Lisle [10]; Roberts [16]; Bergbauer et al, [3]; Ozgen et al, [15]). Seismic anisotropy analysis is an efficient tool to characterize fracture anisotropy and relating seismic anisotropy to fracture densities has been the purpose of the application (Lynn et al, [11]; Shen et al, [17]). If information extracted from seismic anisotropy is reliable, the good quality of seismic data with far offset and wide azimuths along with certain assumptions of data processing are needed.…”
Section: Introductionmentioning
confidence: 99%